Influences of the ZrC coating process and heat treatment on ZrC-coated kernels used as fuel in Pu-burner high temperature gas-cooled reactor in Japan. Issue 1 (2nd January 2021) - Aihara, Jun; Ueta, Shohei; Honda, Masaki; Mizuta, Naoki; Goto, Minoru; Tachibana, Yukio; Okamoto, Koji
ABSTRACT: The concept of Pu-burner high temperature gas-cooled reactor (HTGR) has been proposed to more safely reduce the amount of recovered Pu. In the Pu-burner HTGR concept, coated fuel particles with ZrC-coated yttria-stabilized zirconia containing PuO2 (PuO2 -YSZ) kernels are employed for very high burn-up and high nuclear proliferation resistance. The role of ZrC layer is that of oxygen getter. CeO2 -YSZ kernels were fabricated to simulate the PuO2 -YSZ kernel and coated with a ZrC layer. In this study, we clarified that both Ce-rich grains and Zr-rich grains were densely distributed in surface regions of the as-fabricated CeO2 -YSZ kernel. However, we have already clarified that the surface region of the CeO2 -YSZ kernel coated with a ZrC layer was porous and mainly consisted of Zr-rich grains. These experimental results confirmed that Ce-rich grains were selectively corroded during the ZrC coating process. Then, the chemical stability of Zr-rich grains would be higher than that of Pu-rich grains. Thus, it would be more difficult to extract Pu from PuO2 -YSZ kernels (in which almost all grains are Zr-rich) than from PuO2 -YSZ kernels (in which many Pu-rich grains are included). Influences of the sintering of fuel compact on the microstructure of the ZrC-coated CeO2 -YSZ kernel is also reported.